PENGEMBANGAN MEDIA PETCHA BERBASISI GAME EDUKASI PADA MATERI PECAHAN KELAS IV SD - Aisyah Khairina Daffa; Rida Fironika Kusumadewi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The limited availability of interactive digital media for fractions in grade IV elementary schools prompted this development research. The main focus of the research was to create an educational game-based Petcha media that could facilitate the understanding of abstract concepts in a fun way. The research procedure applied the Research and Development method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The results of the feasibility test by material, media, and language experts showed a percentage of 93.3%, so the product was categorized as very valid. Meanwhile, the practicality test obtained very practical results with a percentage of teacher responses of 97% and student responses of 87%, with an average practicality score reaching 92%. These findings prove that the integration of game elements through the Canva and Wordwall applications is effective in increasing active engagement and learning motivation of students. The main conclusion of the study confirms that the Petcha media is feasible and practical to use as a supporting tool for innovative and contextual mathematics learning. This innovation makes a real contribution in minimizing misconceptions and student boredom during the learning process in the classroom. Although limited to online access, this development is an alternative pedagogical solution that is relevant to the demands of 21st-century education, emphasizing aspects of digital interactivity to create meaningful learning experiences for elementary school students in a comprehensive and systematic manner, and supporting the achievement of optimal teaching quality for all. ABSTRAK Rendahnya ketersediaan media digital interaktif pada materi pecahan kelas IV sekolah dasar memicu dilakukannya penelitian pengembangan ini. Fokus utama riset adalah menciptakan media Petcha berbasis game edukasi yang mampu memudahkan pemahaman konsep abstrak secara menyenangkan. Prosedur penelitian menerapkan metode Research and Development dengan model ADDIE yang mencakup tahap analisis, desain, pengembangan, implementasi, hingga evaluasi. Hasil uji kelayakan oleh para ahli materi, media, dan bahasa menunjukkan persentase sebesar 93,3%, sehingga produk masuk kategori sangat valid. Sementara itu, uji kepraktisan memperoleh hasil sangat praktis melalui persentase respon guru sebesar 97% dan respon siswa sebesar 87%, dengan nilai rata-rata kepraktisan mencapai 92%. Temuan ini membuktikan bahwa integrasi unsur permainan melalui aplikasi Canva dan Wordwall efektif dalam meningkatkan keterlibatan aktif serta motivasi belajar peserta didik. Simpulan utama penelitian menegaskan bahwa media Petcha layak dan praktis digunakan sebagai alat pendukung pembelajaran matematika yang inovatif dan kontekstual. Inovasi ini memberikan kontribusi nyata dalam meminimalisir miskonsepsi serta kejenuhan siswa selama proses pembelajaran di kelas. Meskipun terbatas pada akses daring, pengembangan ini menjadi alternatif solusi pedagogis yang relevan dengan tuntutan pendidikan abad ke-21 yang menekankan aspek interaktivitas digital guna menciptakan pengalaman belajar bermakna bagi siswa sekolah dasar secara komprehensif, sistematis, serta mendukung tercapainya kualitas pengajaran optimal bagi semua.